2017
DOI: 10.1007/s00449-017-1876-x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of chitosan-bead support materials with l-lysine and l-asparagine for α-amylase immobilization

Abstract: Maltose syrups have got wide-range utilizations in a variety of applications from bakery to drug-development. α-Amylases are among the most widely utilized industrial enzymes due to their high specificity in production of maltose syrup from starch. However, enzymes are not stable in ex vivo conditions towards alteration in pH, temperature, and such other parameters as high salt concentrations and impurities, where immobilization is required to advance the stability of the enzyme with which approach the require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
5
2
Order By: Relevance
“…Although high immobilization rates are counted, not all enzymes are available for process of starch breaking. The immobilization efficiencies achieved with IP and IPG beads were higher than those of Yazgan et al [26] , which reported 75.7% efficiency of commercial α -amylase Termamyl® immobilized on chitosan beads. Sharma et al [27] reported α -amylase from A. oryzae was successfully immobilized in calcium agar beads with a high immobilization efficiency of 80%.…”
Section: Resultscontrasting
confidence: 64%
See 2 more Smart Citations
“…Although high immobilization rates are counted, not all enzymes are available for process of starch breaking. The immobilization efficiencies achieved with IP and IPG beads were higher than those of Yazgan et al [26] , which reported 75.7% efficiency of commercial α -amylase Termamyl® immobilized on chitosan beads. Sharma et al [27] reported α -amylase from A. oryzae was successfully immobilized in calcium agar beads with a high immobilization efficiency of 80%.…”
Section: Resultscontrasting
confidence: 64%
“…Sharma et al [27] reported α -amylase from A. oryzae was successfully immobilized in calcium agar beads with a high immobilization efficiency of 80%. However, the overall active immobilization in the IP support of 17.18% was lower than the 24% reported by Yazgan et al [26] . The lower active immobilized enzyme in the support may have resulted in the lower overall immobilization rate, even with a high efficiency of immobilization.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…To increase the cytocompatibility of CS materials, many experimental and theoretical studies have been used to modifying the CS. Particularly, in recent year, the introduction of amino acid moieties to the CS generates some interesting synergistic characteristics for expanding the application scope of CS, such as l-asparagine, l-arginine or l-lysine [ 11 13 ]. Arginine (Arg) is considered as one important amino acids in young mammals, and it can regulates cell division, immune function, and hormone release [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To increase the cytocompatibility of CS materials,many experimental and theoretical studies have been used to modifying the CS. Particularly, in recent year, the introduction of amino acid moieties to the CS generates some interesting synergistic characteristics for expanding the application scope of CS, such as l-asparagine, l-arginine or l-lysine [12][13][14] . L-Arginine (Arg), as the crucial functional components of cell-penetrating peptides, has aroused general concern 15 .…”
Section: Introductionmentioning
confidence: 99%